Volume-outcome relationship and minimum volume regulations in the German hospital sector: Evidence from nationwide administrative hospital data for the years 2005-2007 - Corinna Hentschker; Roman Mennicken; Antonius Sebastian Reifferscheid; Jürgen Wasem; Ansgar Wübker (Health Economics Review, 2018)
Background: This paper analyses the volume-outcome relationship and the effects of minimum volume regulations in the German hospital sector. Methods: We use a full sample of administrative data from the unselected, complete German hospital population for the years 2005 to 2007. We apply regression methods to analyze the association between volume and hospital quality. We measure hospital quality with a binary variable, which indicates whether the patient has died in hospital. Using simulation techniques we examine the impact of the minimum volume regulations on the accessibility of hospital services. Results: We find a highly significant negative relationship between case volume and mortality for complex interventions at the pancreas and oesophagus as well as for knee replacement. For liver, kidney and stem cell transplantation as well as for CABG we could not find a strong association between volume and quality. Access to hospital care is only moderately affected by minimum volume regulations. Conclusion: The effectiveness of minimum volume regulations depends on the type of intervention. Depending on the type of intervention, quality gains can be expected at the cost of slightly decreased access to care.
Keywords: I12; I18; 330; Volume; Hospital quality; Mortality; Access to care